2018
DOI: 10.1007/s13205-018-1338-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficient phosphate accumulation in the newly isolated Acinetobacter junii strain LH4

Abstract: Phosphate (PO) accumulation associated with bacteria contributes to efficient remediation of eutrophic waters and has attracted attention due to its low cost, high removal efficiency and environmental friendliness. In the present study, we isolated six strains from sludge with high concentrations of chemical oxygen demand, total nitrogen and total phosphorus levels. Among them, strain LH4 exhibited the greatest PO removal ability. Strain LH4 is typical of based on physiological, biochemical, and molecular anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…It has been reported that polyphosphate regarded as high-energy compound could be hydrolyzed when phosphorus accumulating bacteria undergo undernourished conditions (Wan et al, 2017;Li and Dittrich, 2019;Zhong et al, 2019). Previous literatures have reported that some bacteria belonging to Acinetobacter genus harbor the ability to synthesize polyphosphate and could be regarded as phosphorus accumulating bacteria (Keating et al, 2016;Han et al, 2018). Therefore, we can conclude that one part of soluble phosphorus can be used for the formation of bacterial substance (e.g., DNA and RNA), and another part of soluble phosphorus can be applied for the synthesis of polyphosphate during inorganic phosphorus solubilization.…”
Section: Deciphering Phosphorus Track During Inorganic Phosphorus Solmentioning
confidence: 99%
“…It has been reported that polyphosphate regarded as high-energy compound could be hydrolyzed when phosphorus accumulating bacteria undergo undernourished conditions (Wan et al, 2017;Li and Dittrich, 2019;Zhong et al, 2019). Previous literatures have reported that some bacteria belonging to Acinetobacter genus harbor the ability to synthesize polyphosphate and could be regarded as phosphorus accumulating bacteria (Keating et al, 2016;Han et al, 2018). Therefore, we can conclude that one part of soluble phosphorus can be used for the formation of bacterial substance (e.g., DNA and RNA), and another part of soluble phosphorus can be applied for the synthesis of polyphosphate during inorganic phosphorus solubilization.…”
Section: Deciphering Phosphorus Track During Inorganic Phosphorus Solmentioning
confidence: 99%
“…Since the 1980s, Acinetobacter has been recognized as a highly efficient bacterium for phosphorus removal and has played a significant role in wastewater treatment processes [ 33 ]. Acinetobacter ’s release of organic acids and phosphatases facilitates the breakdown of PolyP, releasing soluble phosphate [ 34 , 35 ]. Thus, Acinetobacter nosocomialis D-3 holds promise as an efficient bacterium for degrading APP and can be utilized to remedy APP-based flame retardants.…”
Section: Resultsmentioning
confidence: 99%
“…Different from the known potential partial denitrifiers ( Thauera and Halomonas ) detected in the PDN systems, our pilot system enriched the genera of Acinetobacter (17.8 ± 15.5)% and Comamonadaceae (6.7 ± 3.4%), with the very low level of conventional nitrifiers detected (< 0.2%). The species Acinetobacter junii were previously reported to exhibit the ability of efficient N- and P-removal, respectively (Han et al, 2018; Ren et al, 2014). Moreover, rather than the common chemical analysis of the overall PHA variation, we applied the single- cell Raman spectroscopy technique to accurately reveal the existing dominant microorganism (the potential Acinetobacter sp.)…”
Section: Resultsmentioning
confidence: 99%